Value systems and participation in drug trafficking activities in Sonora, Mexico - Francisco Manuel Piña-Osuna (Íconos)
In recent decades, drug trafficking has been identified by many sources as the primary crime problem in Latin America. By the same token, sources have warned of increasing indices and a process of socialization of this activity. The value systems transmitted by this criminal modality have become embedded in some sectors of society, vindicating it and generating approval and a desire to choose this way of life, motivating people to enter this activity. The objective of this article is to identify the value systems of a group of people in drug trafficking, as well as to explore the relationship that these values had on their entry into the activity. A qualitative methodology was used based on convenience sampling and semi-structured interviews with eight subjects incarcerated for this crime in the state of Sonora, along the northern border of Mexico. The findings show that responsibility, intelligence, work, respect, loyalty, and family support enabled these subjects to positively evaluate drug trafficking; these values were recognized as elements that facilitated their entry into illicit work. It is concluded that actions to deal with the negative effects of criminal cultural expressions should clearly differentiate between transgressive and prosocial value systems.